Pengaruh Pajak Hotel, Pajak Restoran, Pajak Hiburan Dan Pajak Penerangan Jalan Terhadap Pendapatan Asli Daerah Kabupaten Karawang Tahun 2019-2023 - Ekky Gilang Pamungkas; Nunung Nurhasanah; Solehudin Solehudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was conducted to examine the effect of hotel tax, restaurant tax, entertainment tax, and street lighting tax on Karawang Regency's original regional income in 2019 – 2023. The issues discussed are (1) How do hotel taxes, restaurant taxes, entertainment taxes, street lighting taxes work? and local revenue at the Regional Revenue Agency (BAPENDA) of Karawang Regency for the period 2019 – 2023, (2) Does hotel tax have a partial effect on local revenue of Karawang Regency in 2019 – 2023, (3) Does restaurant tax have a partial effect on real income Karawang Regency area in 2019 – 2023, (4) Does the entertainment tax have a partial effect on the original local income of Karawang Regency in 2019 – 2023, (5) Does the street lighting tax have a partial effect on the original local income of Karawang Regency in 2019 – 2023 and ( 6) Do hotel taxes, restaurant taxes, entertainment taxes and street lighting taxes have a simultaneous effect on Karawang Regency's original regional income for 2019 – 2023. The data used in the research was obtained from the 2019 – 2023 Budget Realization Performance Report (LRA). The data analysis technique used is multiple linear regression, with a sample of 60 and the sampling method used in this research is purposive sampling. The results of this research show that hotel tax, restaurant tax, entertainment tax, street lighting tax and local revenue at the Karawang Regency Regional Revenue Agency (BAPENDA) for the 2019 – 2023 period are in the poor category. This is because socio-economic conditions are experiencing pressure due to the Covid-19 pandemic resulting in regional income decreasing very significantly. The partial effect results show that Hotel Tax has a significant effect on Karawang Regency's original regional income in 2019-2023, Restaurant Tax has no effect on Karawang Regency's original regional income in 2019-2023, Entertainment Tax has a significant effect on Karawang Regency's original regional income in 2019-2023 and Street Lighting Tax does not have a significant effect on Karawang Regency's original regional income in 2019-2023. Meanwhile, simultaneously it shows that there is an influence of hotel tax, restaurant tax, entertainment tax and street lighting tax on the Karawang district's original regional income.